Research of Soil Moisture Retrieval Algorithms for Processing Radiometry Data - Anh, Vo Thi Lan; Chung, Doan Minh; Ngoc, Ngo Tuan; Kostov, K. G. (Communications in Physics, 2016)
Since 2012, the experts of Space Technology Institute have carried out the field experiments to obtain a high-resolution dataset of microwave radiometers for land surface parameters (soil moisture, soil temperature, vegetation water content), in order to improve the soil moisture retrieval methodology. L-band radiometers were used for measuring the brightness temperature of the bare soil. Field experiments for passive microwave remote sensing of soil moisture were carried out in Hoai Duc District in 2012. L-band microwave radiometers were used for measuring the microwave emission of bare agricultural fields. The radiometers, which are used for soil moisture measurement, worked well during the experimental campaign and produced volumetric soil moisture estimates that compared well with the ground-truth measurements. Explanations for the observed discrepancies are presented. The experimental results showed that the model of Choudhury et al. for surface roughness correction provides a better fit to radiometric data over the angular range between 20° and 50° for \(n = 0\) (i.e., the \(\cos ^{2}θ\) factor in the exponential in (15) is suppressed). Based on the results of the experiments conducted over two experimental sites with different soils, namely sandy loam at Hoai Duc Agrometeorologyl Center, it may be concluded that the testing of both the radiometric equipment and the method for soil moisture retrieval was very successful, and the main goal of the experiments was fulfilled.